[Rafa on the train tracks] - Rocco Murillo::::::photographer::: (2005)
Description supplied by photographer: 'Mi amigo Rafa caminando por las vías del tren que pasan por donde nosotros vivimos en Paso Robles. Me gusta como el esta caminando.' Translation of description: 'My friend Rafa is walking on the train tracks that run next to where we live in Paso Robles. I like how he is walking.'